2018
DOI: 10.2147/cia.s152701
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, prospective interventional study of the tolerability and efficacy of 0.4 mg oral tamsulosin oral controlled absorption system in men with lower urinary tract symptoms associated with benign prostatic hyperplasia who are unsatisfied with treatment with 0.2 mg tamsulosin

Abstract: PurposeThe aim of this study was to investigate the efficacy and tolerability of switching from 0.2 mg tamsulosin to 0.4 mg tamsulosin oral controlled absorption system (OCAS) over a 12-week period in Taiwanese men with lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH).Patients and methodsTaiwanese male patients who were dissatisfied with treatment with 0.2 mg tamsulosin were enrolled in this clinical study and switched to 0.4 mg tamsulosin OCAS. Efficacy was assessed over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In this study, we were not able to compare the individuals in the combination group with the placebo control because PE patients who have eagerly waited for effective treatments usually have a higher dropout rate when the therapy is suboptimal, with the dropout rates in some reports even reaching 70.6% (Jern et al, ). Furthermore, the adverse events rate of the 0.4 mg dose of tamsulosin was as high as 11%~14.11%, which may further increase the loss of follow‐up with patients whose primary purpose was to treat premature ejaculation (Kim, Han, Sung, Choo, & Lee, ; Yang, Chen, Hou, Lin, & Tsui, ). Thus, we chose a 0.2 mg dose of tamsulosin and not a 0.4 mg dose as the appropriate dosing schedule in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we were not able to compare the individuals in the combination group with the placebo control because PE patients who have eagerly waited for effective treatments usually have a higher dropout rate when the therapy is suboptimal, with the dropout rates in some reports even reaching 70.6% (Jern et al, ). Furthermore, the adverse events rate of the 0.4 mg dose of tamsulosin was as high as 11%~14.11%, which may further increase the loss of follow‐up with patients whose primary purpose was to treat premature ejaculation (Kim, Han, Sung, Choo, & Lee, ; Yang, Chen, Hou, Lin, & Tsui, ). Thus, we chose a 0.2 mg dose of tamsulosin and not a 0.4 mg dose as the appropriate dosing schedule in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Recent studies have reported that increasing the dose of tamsulosin to 0.4 mg is effective and safe in Asian men with LUTS who do not respond to an initial dose of 0.2 mg tamsulosin. 9 , 10 , 11 , 12 However, it is still unclear whether tamsulosin 0.4 mg as the initial dose is effective and safe in Asian men with LUTS. To the best of our knowledge, only one randomized clinical, double-blind, phase 3 trial has been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Aging is a physiological process associated with dysfunction of the autonomic nervous system. 6 , 7 The physiological response to anesthesia may be unpredictable and paradoxical if the autonomic nervous system is dysfunctional. ATP, the principal messenger released from urothelial cells, is a co-transmitter together with noradrenaline in sympathetic nerves and acetylcholine in parasympathetic nerves and considered a potential therapeutic target for functional bladder functional disorders.…”
Section: Introductionmentioning
confidence: 99%